FOREIGN EXPERIENCE IN IMPLEMENTING ISLAMIC BANKING SERVICES IN THE ACTIVITIES OF COMMERCIAL BANKS (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article examines international experience in integrating Islamic (Shariah-compliant) banking services into the operations of commercial banks. It reviews the main implementation models — Islamic windows, Islamic banking branches, full-fledged conversion, and dual-banking systems — and compares regulatory frameworks, operational practices, product adaptation, governance, and market outcomes across representative countries. Case studies include Malaysia, Turkey, Pakistan, and the United Kingdom. The article draws lessons for commercial banks considering introduction of Islamic services: legal clarity, strong Shariah governance, product innovation, staff and systems readiness, risk-management adaptation, and customer education. Key empirical findings indicate that hybrid approaches (Islamic windows and branches) allow rapid market entry but require robust segregated accounting and governance to avoid reputational and compliance risks. Policy recommendations are offered for banks and regulators pursuing Islamic banking inclusion.
Keywords: Islamic banking; Islamic windows; participation banks; dual banking; Shariah governance; commercial banks; Malaysia; Turkey; Pakistan; United Kingdom.